Population, Power, and Plurality: A Critical Assessment of Nepal’s Social Demography - Sigdel, Uddhav; Kafle, Rameshwor; Sunuwar, Man Bahadur; Thapa, Tara Bahadur (Ganeshman Darpan, 2026)
Social demography, the systematic study of the interplay between population dynamics and social structure, social inequality, social identity, and social power, plays a fundamental role in the social sciences. Nepal is one of the most analytically fascinating and demographically complex countries in South Asia, a small, landlocked, multi-ethnic, and constitutionally transitional one that has been rapidly and simultaneously transiting in all directions in terms of changes in fertility, mortality, migration, urbanization, and ethnicdemographic composition over the last 30 years. Although there is a wide literature on demography in Nepal, it has been scattered in various disciplines, from positivist demography, political anthropology, migration studies, and development economics; there is little theoretically integrated synthesis of the literature. Furthermore, previous reviews focus disproportionately on overall national demographic data and fail to sufficiently address the structures of social inequalities such as caste, ethnicity, gender, and geography, which are integral to Nepal’s demography, rather than merely contextual. In this paper, the peer-reviewed scholarly articles about the topic of social demography in Nepal, which were published between 2000 and 2026, will be discussed in terms of important debates, research methodology, and socio-political issues. Thirty-five academic papers consisting of journal articles, monograph books, census studies, and policy reports, found through academic databases such as Scopus, Web of Science, JSTOR, and demographic publications, have been analyzed through thematic and intersectional perspectives. The findings suggest that there has been a fast pace of demographic transition in Nepal. The study presents an integrated demographic transition theory for stratified populations by incorporating classic demographic transition theory with an analysis of societal stratification. This theory addresses the dynamics of Nepal’s population, taking into account the dimensions of caste, ethnicity, gender, and geography.